Incidence of ANCA-associated vasculitis in a UK mixed ethnicity population - Pearce, Fiona A; Lanyon, Peter C.; Grainge, Matthew J.; Shaunak, Reena; Mahr, Alfred; Hubbard, Richard B.; Watts, Richard A (Oxford University Press, 2016)
Objectives: We aimed to estimate the incidence of ANCA-associated vasculitis in the UK and how this varied by ethnic group. Methods: We identified incident cases of ANCA-associated vasculitis between March 2007 and June 2013 in the Nottingham–Derby urban area from medical records using multiple sources. We derived the denominator population from the 2011 census, and we calculated incidence rate ratios using Poisson regression. Results: Overall, we identified 107 cases of ANCA-associated vasculitis, giving an incidence of 23.1 per million person-years (95% CI: 18.9, 27.9). The incidence among the white population was 25.8 per million person-years (95% CI: 21.0, 31.3) and among the black and minority ethnic (BME) population 8.4 per million person-years (95% CI: 3.1, 18.3). After adjustment for age and sex, the difference between ethnic groups was not statistically significant (incidence rate ratio 0.7, 95% CI: 0.3, 1.5, P = 0.3). Conclusion: Overall, the incidence of ANCA-associated vasculitis was similar to other epidemiological studies. Crude incidence rates were lower in the BME than in the white population, but this was partly explained by the older age profile among the white compared with BME population.